Experimental evaluation of sustainable jute–basalt hybrid FRP systems for flexural strengthening of RC beams with variable wrapping and light-weight aggregate replacement - Panumas Saingam; Muhammad Adnan Hanif; Fahad Ahmed; Burachat Chatveera; Gritsada Sua-iam; Ali Ejaz; Qudeer Hussain; Preeda Chaimahawan; Chisanuphong Suthumma; Anwar Ahmad (Scientific Reports, 2026)
This research experimentally assesses the flexural strengthening of reinforced concrete (RC) beams through the use of sustainable jute–basalt (JB) hybrid fiber-reinforced polymer (FRP) systems with variable wrapping schemes and lightweight aggregate (LWA) replacement. A total of 18 beams with identical geometry and reinforcement were tested under four-point bending, including controls, basalt FRP (BFRP), jute FRP (JFRP), and hybrid JB FRP systems in bottom-only, U-wrap, and full-wrap configurations. The results indicate that FRP confinement significantly modified failure modes, transitioning from the brittle crushing in controls to rupture- or debonding-controlled mechanisms. BFRP significantly enhanced strength, achieving up to 36.8% greater capacity in full-wrap beams, while JFRP improved ductility but was more prone to premature debonding. Hybrid JB FRP systems demonstrated the most balanced performance, with U-wrap hybrids achieving 39.6% higher load capacity and maintaining significant deformation capacity even in LWA concrete. Load–strain responses confirmed yielding of steel reinforcement in all cases, though maximum strains were reduced after confinement due to premature fiber debonding or rupture at smaller deflections. The use of LWA reduced ductility of control beams, but hybrid U-wrap systems successfully compensated for this limitation, providing the highest load and deflection values among all specimens. These results emphasize the potential of hybrid natural–mineral FRP systems as sustainable alternatives to synthetic composites, providing competitive ductility and reinforcement for structural retrofitting applications in both conventional and lightweight concretes.
Keywords: Structural Behavior of Reinforced Concrete; Masonry and Concrete Structural Analysis; Innovative concrete reinforcement materials